Sentiment Analysis of Movie Reviews: A Study of Machine Learning Algorithms with Various Feature Selection Methods - Kaur, Rajwinder; Verma, Prince (International Journal of Computer Sciences and Engineering, 2025)
Nowadays, with rapid use of internet, a very large number of reviews are posted by visitors on different website related to the various movies that describe the polarity between movies. Customers share their feelings with others in the form of comments or reviews that describe their opinion as either in negative or in positive or in neutral. Such websites are essential to people for decision making. In this paper, the sentiment analysis is done in order to analyze the movie reviews, so we use the machine learning classifier Random Forest with Gini Index based Feature Selection and also compared it with another algorithm such as SVM. The results show that Gini Index method with Random Forest classifier has better performance in terms of Accuracy, Root Mean Square Error, Precision, Recall and F-Measure.